2015
DOI: 10.1007/s12665-015-4412-9
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous carbonation of the potassium-depleted residue from potassium feldspar–CaCl2 calcination for CO2 fixation

Abstract: Based on the academic thought of carbon capture and utilization, a novel process to integrate the potassium extraction from the insoluble potassium feldspar, industrial waste utilization, and the subsequent CO 2 fixation using the resultant potassium-depleted residue was proposed in our previous studies. The potassium-depleted residue comprises several Ca-bearing phases, namely wollastonite (CaSiO 3 ), pseudowollastonite (Ca 3 Si 3 O 9 ), Clmayenite (Ca 12 Al 14 O 32 Cl 2 ), and anorthite (CaAl 2 Si 2 O 8 ), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Other studies reported more complicated product phases, including Ca 12 Al 14 O 33 and Ca 12 Al 14 O 32 Cl 2 [34,38], appearing in the CaCl 2 /K-feldspar system. In their investigations, air was directly introduced into the calcination system without drying pretreatment.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Other studies reported more complicated product phases, including Ca 12 Al 14 O 33 and Ca 12 Al 14 O 32 Cl 2 [34,38], appearing in the CaCl 2 /K-feldspar system. In their investigations, air was directly introduced into the calcination system without drying pretreatment.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Most of the literature that has adopted the roasting–leaching process has suggested calcium chloride as the best roasting agent on the basis of potassium recovery. , In all these studies, laboratory-grade calcium chloride was used.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, there are several methods of reducing CO 2 emissions in the atmosphere, such as the CO 2 capture and storage (CCS) technology or by utilizing CO 2 as a chemical raw material (Aresta 2010;Barrow 1973;Hou et al 2014;Klotz and Rosenberg 1950;Liu et al 2014;Sheng et al 2015;Xie et al 2014aXie et al , 2015aZhang et al 2015b). To mitigate the adverse effect on the environment and ensure the sustainable use of fossil energy, numerous studies have been carried out to sequestrate CO 2 underground Zhang et al 2015a).…”
Section: Introductionmentioning
confidence: 99%